2000
DOI: 10.1375/136905200320565580
|View full text |Cite
|
Sign up to set email alerts
|

Maternal metabolic abnormalities in twin–to–twin transfusion syndrome at mid–pregnancy

Abstract: We r epor t abnor mal mater nal l abor ator y par ameter s i n tw i n-to-tw i n tr ansfusi on syndr ome (TTTS) at mi d-pr egnancy. A r etr ospecti ve char t r evi ew w as under tak en of 109 pati ents w i th TTTS eval uated for pl acental l aser sur ger y. Compl ete bl ood count (CBC), bl ood type and Rh factor, ur i ne anal ysi s and ser um chemi str y panel w er e obtai ned pr eoper ati vel y, w i th the CBC and ser um al bumi n r epeated on the fi r st postoper ati ve day. The mean gestati onal age w as 21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…This speculation is underlined by the fact that even in the most severe cases of a fall in maternal hemoglobin and hematocrit, there were no clinical signs of traumatic blood loss, such as tachycardia, hypotension and dizziness. Physicians must be aware of this phenomenon, which was described previously by De Lia et al [3], to avoid unnecessary invasive diagnostic and therapeutic procedures. Furthermore, to our knowledge this is the first study to demonstrate in vivo the correlation between the drained amniotic fluid volume and the difference in maternal hemoglobin and hematocrit before and after the procedure.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This speculation is underlined by the fact that even in the most severe cases of a fall in maternal hemoglobin and hematocrit, there were no clinical signs of traumatic blood loss, such as tachycardia, hypotension and dizziness. Physicians must be aware of this phenomenon, which was described previously by De Lia et al [3], to avoid unnecessary invasive diagnostic and therapeutic procedures. Furthermore, to our knowledge this is the first study to demonstrate in vivo the correlation between the drained amniotic fluid volume and the difference in maternal hemoglobin and hematocrit before and after the procedure.…”
Section: Discussionmentioning
confidence: 83%
“…De Lia et al [3] reported several maternal metabolic abnormalities in severe TTS in their series of fetoscopic laser coagulation, performed via maternal laparotomy under general anesthesia, suggesting that the onset of TTS seems to involve disturbances in the maternal metabolism as well. Elevated concentrations of interleukin-6 (IL-6) and ·-fetoprotein (AFP) in the amniotic fluid of structurally normal fetuses have been associated with preterm delivery and fetal jeopardy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These changes are not explained by perioperative complications or by the minimal load with intravenous crystalloids, which was no more than 0.8% of the mean body weight. De Lia et al 12 previously reported similar suboptimal volume expansion associated with TTTS and haemodilution subsequent to treatment, but mechanisms remained to be discussed.…”
Section: Discussionmentioning
confidence: 97%
“…As amniotic fl uid proteins are mainly a transplacental fi ltrate of maternal plasma proteins, the lower albumin and total protein levels could be explained by a dilution of the fi ltrate due to polyuria of the recipient twin. However, in a series of 109 patients undergoing placental laser surgery for TTTS at midpregnancy, De Lia et al [9] found hypoproteinemia in all TTTS mothers. This suggests that our fi ndings could be at least in part a refl ection of the changed maternal protein content.…”
Section: Discussionmentioning
confidence: 97%